The image of Christian unity in the theological thought of Dietrich Bonhoeffer - Julia Shtonda (Вестник Свято-Филаретовского института, 2022)
The article is devoted to the analysis of the theme of the church’s unity in the theological works and pastoral practice of the German theologian and martyr pastor Dietrich Bonhoeffer. Bonhoeffer was a member of ecumenical organizations and congresses, collaborated with representatives of various Christian denominations. During the years of the Hitler regime, Bonhoeffer was a member of the Confessing Church and sought to build the unity of the church on evangelical foundations. The theological understanding of the church’s unity is revealed in Bonhoeffer’s dissertation Sanctorum Communio, in which he comprehends the phenomenon of the Christian community using sociological terms. The image of the Church presented in the dissertation as a community in which the presence of Christ is revealed became the leitmotif of Bonhoeffer’s pastoral and teaching activities. It is no coincidence that the most productive period of his theological work was the period of leadership of the theological seminary in Finkenwald, which became for students not only a place to receive a theological education, but also an experience of life in a Christian community. Bonhoeffer interprets the Christian brotherhood as a certain quality of communication between Christians. He defines Christian denominations as a way of confessing faith in the visible Christian community, while the mystical organism of the Church is on the other side of the denominations; the concept of denominations is not theological, but it has a social, political, historical significance. Christian unity for Bonhoeffer is inextricably correlated with the practice of Christian life through the creation of communities and the acquisition of brotherly relations with other Christians.